Implementasi Model Pembelajaran Project-Based Learning Terhadap Profil Pelajar Pancasila Peserta Didik Pada Materi Struktur Dan Fungsi Tubuh Makhluk Hidup Kelas 8 SMP Negeri 7 Banjarmasin - Anida Tri Nastiti; Yudha Irhasyuarna; Yasmine Khairunnisa (CV.ITTC INDONESIA, 2025)
The purpose of this study was to determine the impact of the implementation of the project-based learning model on the Pancasila student profile of students in the material of the structure and function of the body of living things. This study is a type of action research in the classroom (classroom research) to overcome problems in the classroom. The subjects of the study were students from Class VIII D of the odd semester for the 2024/2025 academic year, with a total of 37 students at SMP Negeri 7 Banjarmasin. This study was conducted in two cycles, each cycle reflected in the specified actions. Data collection techniques used observation sheets, tests, project assignments, and documents. The results of the study indicate that the implementation of the learning model in the Pancasila student profile has a significant impact on increasing the attitude of reciprocal cooperation and creativity of students, and that the PjBL model is effectively used for learning because it does not damage student learning outcomes. This can be seen from the results of the study in cycle I and cycle II which experienced an increase in both the attitude of mutual cooperation and creativity as well as the value of student learning outcomes which were overall declared complete